Case study of underachievers in a co-operative learning classroom - Pang, Siu San (2008)
The research is an exploratory case study on underachievement in primary pupils in Singapore. The two main purposes of the research were firstly, to identify the causes of underachievement among primary pupils and, secondly, to use co-operative learning strategies in attempts to reverse underachievement. The study was undertaken in a Primary 4 class of 38 pupils whereby three pupils were identified as underachievers based on certain criteria. These three underachievers were observed systematically over a period of nine months so as to identify the causes of their underachievement and implement strategies to reverse their underachievement. Multiple sources of information were tapped to provide a complete picture of the underachievers. Four factors (personality characteristics, home background, peer and school environment) were found to have contributed to their underachievement. With implementation of a co-operative learning environment in the class for six months, the peer and school factors appeared to have effected positive behavioural changes and academic improvement among the underachievers. The classroom environment instrument "My Class Inventory" was used to assess the classroom climate. It was found that the pupils perceived the class to be cohesive and were motivated to learn.